Residual effect of INM on mungbean (Vigna radiata) growth, yield uptake and nutrient balance - N, NIRANJAN B; N, KISHOR; S, PRAKASH S; KUMARASWAMY, SUNIL (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during rainy (kharif) season of 2019–20 and summer season of 2020–21 at Byrasandra village, Karnataka to study the residual effects of integrated nitrogen management (INM) in maize (Zea mays L.) on succeeding mungbean [Vigna radiata (L.) R. Wilczek] growth, yield, and soil properties. The residual effect of treatment involving 75% recommended dose of nitrogen (RDN) + 50% recommended dose of farmyard manure (RD FYM) +25% RDN through vermicompost to kharif maize resulted in significant (P<0.05) taller mungbean plants (25.4 cm), more leaves (16.0), increased pod count (21.7), longer pods (9.7 cm), higher test weight (4.4 g), seed yield (880.4 kg/ha) and haulm yield (1815.8 kg/ha) at harvest compared to the control group. After mungbean harvest, plots treated with 75% recommended dose of nitrogen (RDN) + 50% recommended dose of farmyard manure (RD FYM) + M 25% RDN through vermicompost showed significantly higher uptake of total N, total P, and total K (50.8, 9.3, and 49.1 kg/ha, respectively) compared to the control, improving soil nutrient balance and achieving the highest benefit-cost ratio in Alfisols.